Extraction of phenolic compounds from Citrus hystrix leaves and their antioxidative effects on oil and minced meat of sardine (Sardinella lemuru bleeker) - Abdulkadir Gedi, Mohamed (2011)
Optimization of extraction methods for extracting antioxidant and phenolic rich compounds from Citrus hystrix leaves was carried out by supercritical carbon dioxide (SC-CO2) using response surface methodology (RSM). The conventional EtOH extraction was used as the control. The effects of CO2 flow rate (15-25 g/min), extraction pressure (100-300 bar) and extraction temperature (40-60 °C) on yield, total phenolic content (TPC) and Diphenylpicrylhydrazyl (DPPH-IC50) were determined. Optimized extracts by SC-CO2 and that of ethanol were analyzed by HPLC for the recovery of bioactive phenolic acids (Vanillic, p-Coumaric, m-Coumaric, Sinapic, Benzoic and trans-Cinnamic acid). The extracted phenolics were used as natural antioxidants to retard sardine (Sardinella lemuru) lipid oxidation. Different concentrations of the extracts (0.1%, 0.2%, 0.3%, and 0.4%), control (without antioxidant) and positive control (BHT-0.02%) were added to the extracted oil and refrigerated (4 °C) mince of sardine. Their peroxide values (PV) as well as thiobarbituric acid (TBA) values were determined. Among the three extraction variables studied, extraction pressure was the most critical factor which influenced the yield, TPC and DPPH-IC50 (p< 0.001) of the extracts,followed by CO2 flow rate (p<0.05) and extraction temperature (p<0.05). The optimum conditions for extractions were pressure at 267 bars, CO2 flow rate at 18g/ml and temperature at 50 °C. Their corresponding responses for yield,TPC and DPPH-IC50 were 5.046%, 116.558 mg GAE/g extract and 0.064 mg/mL, respectively. These values were reasonably close to their predicted values (p>0.05) with high overall coefficient of determination (R2>0.8). R2 values for yield, TPC, and DPPH-IC50, were 0.935, 0.95, and 0.96,respectively. Better DPPH-IC50 and TPC were obtained in the extracts using SC-CO2 extraction method whereas higher yield and phenolic acids were obtained with the ethanol extraction. A significant effect (p<0.05) of C.hystrix leaves extracts from SC-CO2, in retarding fish lipid oxidation was apparent. Oxidation stability was linear with increasing concentrations of C.hystrix leaf which were extracts from 0.1 to 0.4%. There were no significant differences in oxidation retardation between the addition of 0.1% and/or 0.2% of the extracts in the storage period; however, both were significantly (p<0.05)different from the control in some cases. Likewise, 0.3 and 0.4% exhibited similar antioxidant inhibitory effects which were remarkably better than those of 0.1 and 0.2% and comparable to those of the commercial antioxidant (BHT).The SC-CO2 optimized C.hystrix leaf extracts may thus be considered as a probable promising new source of antioxidants in marine lipids.